Innovation As The Competitiveness Of Maritime Universities In Semarang - Agus Aji Samekto; Lilik Kustiani; Syaiful Arifin (Pusat Riset dan Inovasi Nasional, 2023)
Increasingly fierce competition causes university managers, both private universities (PTS) and public universities (PTN), to maximize existing resources. Not only on resource management but also must pay attention to the ability of each unit or part of the college that has selling value to the community, has something different from competitors and also pays attention, implements regulations from the government and has differentiation. Innovation gets the attention of maritime universities in Semarang by making continuous improvements. In addition to continuous improvement, they also make overall changes. The competitive advantage of maritime universities in Semarang is able to provide the best quality by getting a quality standard assessment from IMO, ISO, and having an international standard network. Maritime Universities in Semarang are universities that have differences compared to universities in general. It is something different and has a uniqueness, but like other universities, massively also has a strategy to increase competitive advantage, so the hope of maritime college in Semarang is to have many and sustainable students.